(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper provides a critical analysis of how Palestinian women’s experiences are represented in Indonesian media, focusing on issues of gender, resistance, and solidarity. While Palestinian women have long been at the forefront of the struggle for Palestinian rights, their stories are often marginalized in mainstream media. This study examines how Indonesian news outlets, social media platforms, and cultural productions frame the role of Palestinian women in the resistance movement, highlighting themes of gendered violence, resilience, and activism. Through content analysis of news reports, documentaries, and feature articles, the research explores the intersections of gender, politics, and international solidarity, particularly within the context of Indonesia’s Muslim-majority identity. The paper also looks at how these media representations affect public perceptions of Palestine in Indonesia, particularly among young people and feminist groups. By investigating the portrayal of Palestinian women as both victims and active agents of change, the paper sheds light on the complex ways in which Indonesian media contribute to global solidarity movements, framing Palestinian women as symbols of resistance and justice.